2019
DOI: 10.1007/s00285-019-01333-8
|View full text |Cite
|
Sign up to set email alerts
|

A simple mechanochemical model for calcium signalling in embryonic epithelial cells

Abstract: Calcium signalling is one of the most important mechanisms of information propagation in the body. In embryogenesis the interplay between calcium signalling and mechanical forces is critical to the healthy development of an embryo but poorly understood. Several types of embryonic cells exhibit calcium-induced contractions and many experiments indicate that calcium signals and contractions are coupled via a two-way mechanochemical feedback mechanism. We present a new analysis of experimental data that supports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 82 publications
3
47
0
Order By: Relevance
“…During embryonic development, cells and tissues generate mechanical forces. The effects of these forces on morphogenetic processes have been linked to Ca 2+ signalling 100, 101 . In addition, the developing notochord of Ciona is known to express ion channels that may transduce mechanical forces into Ca 2+ signals 62 .…”
Section: Resultsmentioning
confidence: 99%
“…During embryonic development, cells and tissues generate mechanical forces. The effects of these forces on morphogenetic processes have been linked to Ca 2+ signalling 100, 101 . In addition, the developing notochord of Ciona is known to express ion channels that may transduce mechanical forces into Ca 2+ signals 62 .…”
Section: Resultsmentioning
confidence: 99%
“…signaling is connected to the regulation of cell mechanics is not currently understood and warrants further investigation. One possibility is that tension impacts the level of gap junction communication between cell and may also influence the activity of mechanosensitive ion channels (Kaouri et al, 2019). Feedback between calcium signaling and cell mechanics may play important roles in ensuring tissue growth and morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These oscillations have been associated with the coupling between the chemical and mechanical signalling [19,11], or the relation between cell polarity and force transmission [18,21], with a potential dependence on the confinement [20]. More recently, it has been observed that the relocation of actomyosin components from medial to junctional areas of the cell may trigger these pulsatile response, suggesting that this biochemical delay between motor molecules is responsible of the observed oscillations [26].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been observed that the relocation of actomyosin components from medial to junctional areas of the cell may trigger these pulsatile response, suggesting that this biochemical delay between motor molecules is responsible of the observed oscillations [26]. Some recent works have analysed the dynamics of the chemo-mechanical coupling through diffusion reaction equations, with applications in apical constriction in epithelia [11], monolayers on substrates [18,21] or wound healing [22]. In order to analyse the stability of such systems, we here focus on the delay and model it explicitly by resorting to a delayed cell rheology and the resulting delay differential equations, in similar manner to the stress analysis in yeast [13], neural axons conduction [3], transport in respiratory systems [5], or in cell maturation [10].…”
Section: Introductionmentioning
confidence: 99%